2013
DOI: 10.1149/2.059304jes
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Bimetallic Ag and Ni Alloys on Each Other's Electrocatalysis to Glucose Oxidation

Abstract: The electrocatalysis of Ag/Ni bimetallic alloys to glucose oxidation was studied. It was found that the presence of Ag and Ni in the alloys facilitates each other's electrocatalysis toward glucose oxidation, exhibiting an interesting synergistic effect. At about 0.7 V vs SCE, the electrocatalysis of Ag toward glucose oxidation was enhanced by Ni. However, it's very difficult to obtain stable response signals at this potential although a relatively large current response to glucose was observed. Similarly, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…At present, more and more alloy research in glucose detection has replaced pure metal to improve the stability by forming bimetallic structure (Mahshid et al, 2013;Miao et al, 2013;Sheng et al, 2014;Vilana et al, 2015). Wang et al (2008) synthesized three-dimensional PtPb alloy networks on Ti substrates to overcome the shortcomings of pure metal and significantly improved the performance.…”
Section: Introductionmentioning
confidence: 99%
“…At present, more and more alloy research in glucose detection has replaced pure metal to improve the stability by forming bimetallic structure (Mahshid et al, 2013;Miao et al, 2013;Sheng et al, 2014;Vilana et al, 2015). Wang et al (2008) synthesized three-dimensional PtPb alloy networks on Ti substrates to overcome the shortcomings of pure metal and significantly improved the performance.…”
Section: Introductionmentioning
confidence: 99%
“…An previous investigation found that potential scanning nano-NiO modified carbon paste electrodes up to high potential in alkaline solution greatly increases the amount of redox couple Ni(OH) 2 /NiOOH derived from NiO, and thus improves their electrochemical properties and electrocatalytical performance toward the oxidation of glucose [16]. The electrocatalysis of Ag/Ni bimetallic alloys to glucose oxidation was studied [17]. It was found that there is a synergistic effect of bimetallic Ag and Ni on each others electrocatalysis toward glucose.…”
Section: Introductionmentioning
confidence: 99%
“…Approaches to sensor formation on GCEs were used by Miao et al [ 76 ] (Ag/Ni); Gholivand and Azadbakht [ 80 ] (Au/Pt); and Chen et al [ 87 ] (Au/Pd). Claims to exploit synergistic effects were made by Miao et al [ 76 ] (Ag/Ni), who commented: “Especially, the presence of Ag improves the elecrocatalytical performance of Ni at lower potential, which facilitates amperometric measurements of glucose and shows the potential to develop glucose based sensors”.…”
Section: Biosensors—grouped By Target Analytementioning
confidence: 99%